Hamartoma of the breast - Murat, A.; Ozdemir, H.; Yildirim, H.; Poyraz, A. K.; Ozercan, R. (Wiley, 2007)
Breast hamartoma is a rare benign tumour that leads to unilateral breast enlargement without a palpable localized mass lesion. Histologically, a hamartoma consists of varying amounts of adipose, gland, fibre and smooth muscle tissue. The characteristic mammographic appearance of hamartoma of breast has distinct mammographic features with circumscription and fat and soft-tissue density surrounded by a thin radiopaque capsule or pseudocapsule. Ultrasonographic findings include a well-defined mass lesion consisting of echogenic and sonolucent areas. We present histopathological and radiological findings of a 42-year-old female patient with breast hamartoma who has no complaint.
Keywords: breast; hamartoma; mammography; ultrasound